Economic Value and Utilization of social media in Fertilizer Sales in Taruna Mandiri Ngemplak Sleman, Yogyakarta - Kusumastuti, Tri Anggraeni; Widiati, Rini; Syahlani, Suci Paramitasari; Wankar, Tian Jihadan; Triatmojo, Agung; Muzayannah, Mujtahidah Anggriani Ummul (Universitas Bengkulu, 2023)
Taruna Mandiri is farmers group that sells cattle and organic fertilizer. Since the Foot and Mouth Disease outbreak, they have relied more on selling organic fertilizers. This research aims to analyze the economic value of selling organic fertilizers and understand the use of social media in selling fertilizers. Selection of the location in the Taruna Mandiri farmers group, Ngemplak District, Sleman Regency. Purposive sampling of 15 out of 40 members who are administrators and manage the manufacture and processing of fertilizers for sale. The research was conducted in a quantitative descriptive method. Primary data retrieval through direct interviews using a questionnaire tool. The primary data taken include respondents' characteristics, livestock ownership, and understanding of the use of social media. The results showed that with 55 cattle ownership, the economic value of selling fertilizer was IDR. 535,000/period or IDR. 2,140,000/month. Farmers group are interested in selling by online because it is useful for expanding the market, adding information, and at the same time promoting products. The social media platforms that farmers want are WhatsApp business, Instagram and Facebook but due to limited knowledge, farmers use the personal WhatsApp platform. The existence of a touch of technology, both in labeling and using the right social media platforms, is very necessary for the group to improve product quality and expand the consumer market.